Flora synopsis of the “Kamenny lake tract” natural monument (Kostanay region) - Sultangazina, G.J.; Kuprijanov, А.N.; Ermekova, D.K.; Utebasova, U.A (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article presents the results of the floristic diversity study of the state natural monument of local significance‒ “Kamenny lake tract” with a total area of 2.5 hectares. According to natural conditions, this territory is included in the subzone of arid forb-feather grass steppes on low-humus southern chernozems and dark chestnut soils, plowed up to 80%. Under the birch forest soils are dark gray, loamy, and sandy; on slopes they are leached chernozem; near-shore soils are meadow-marsh soils. The studies were carried out in 2019-2022. On the basis of field studies, five main ecotopes were identified: shrub thickets on slopes, birch forest on steep slopes, upland meadows with shrub thickets, meadow-marsh communities on coasts, and meadowsteppe communities. A synopsis containing species’ habitat information within the specially protected natural area was compiled. In the study area, the total list of higher vascular plants includes 177 species from 48 families and 132 genera. The leading families are Asteraceae, Rosaceae, Poaceae, Fabaceae, Lamiaceae, and Caryophyllaceae. The basis of the flora is herbaceous plants, followed by woody, aquatic plants. The steppe ecological-coenotic group is the richest by the volume of species. In the flora of the “Kamenny lake tract” a large proportion of species has significant extent areas: cosmopolitan, holarctic, and palearctic. The holarctic and palearctic types are the largest number of species. The Red Book of Kazakhstan species in the study area are Adonis wolgensis, Stipa pennata, and Tulipa biebersteiniana.
«Каменное озеро» табиғи ескерткіші флорасының конспектісі (Қостанай облысы)
Keywords: flora; specially protected natural area; natural monument “Kamenny lake tract”; higher vascular plants; rare and endangered plants